2016
DOI: 10.17576/mjas-2016-2001-01
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antioxidant Activity of Lichens Usnea rubrotincta, Ramalina dumeticola, Cladonia verticillata and Their Chemical Constituents

Abstract: The present study was carried out to evaluate the antibacterial and antioxidant activity of extract and chemical constituents of Usnea rubrotincta, Ramalina dumeticola and Cladonia verticillata. Acetone extract of U. rubrotincta showed promising antibacterial activity against Gram positive bacteria Bacillus subtilis with the lowest Minimal Inhibitory Concentration (MIC) value of (15.63 µg/mL). Six secondary metabolites were isolated using Preparative High Performance Liquid Chromatography (PHPLC) method from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
1
7
1
Order By: Relevance
“…The value of the total phenolics contents (TPC) of the R. capitata acetone extract was high and amounted 670.6376 ± 66.554 µg GAE mg -1 . The obtained value for the total phenol content are considerably higher than those previously published for acetone extract of Ramalina dumeticola (101.62 ± 3.51 mg GAE per g dry extract) (Gunasekaran et al, 2016[ 8 ]). Likewise, lichen from the genus Ramalina , was investigated for its phenolic content.…”
Section: Resultscontrasting
confidence: 63%
“…The value of the total phenolics contents (TPC) of the R. capitata acetone extract was high and amounted 670.6376 ± 66.554 µg GAE mg -1 . The obtained value for the total phenol content are considerably higher than those previously published for acetone extract of Ramalina dumeticola (101.62 ± 3.51 mg GAE per g dry extract) (Gunasekaran et al, 2016[ 8 ]). Likewise, lichen from the genus Ramalina , was investigated for its phenolic content.…”
Section: Resultscontrasting
confidence: 63%
“…Salazinic acid was present in R. conduplicans and R. pacifica while sekikaic acid was present in R. hossei and R. conduplicans. Antimicrobial activity of usnic acid 18,35,51 , salazinic acid 52 and sekikaic acid 26,35,53 have been reported. The study of Cansaran et al 4 showed a direct correlation between the amount of usnic acid and the antimicrobial activity observed.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds are called lichen substances and till now >1000 lichen secondary metabolites have been identified. Many of these compounds are low molecular weight phenolic compounds and are known to protect the lichens by functioning as sunscreen, anti-herbivore etc 21,26 . TLC is one of the techniques used to detect the secondary metabolites present in lichen extracts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[26,58,59] In this study, the TLC showed the presence of two major compounds, viz., atranorin and zeorin. It is shown that atranorin [60][61][62] and zeorin [34] exhibit antimicrobial activity. The observed antimicrobial potential of methanolic extract of H. incana could be endorsed to the presence of these secondary metabolites.…”
Section: Antibacterial Activity Of H Incanamentioning
confidence: 99%